MUSIC THERAPY AS A METHOD OF PSYCHO-CORRECTING AGGRESSION IN ADOLESCENTS - Дробот, О.; Кривенок, Ю. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2019)
This article describes the particularities of applying the music therapy method to reduce aggression in adolescents. It was determined that in the adolescent age, aggressiveness reaches a new level, and its development bears upon the quality of the personality’s orientation toward the future and development of his or her life prospects. The music therapy method capable of stabilizing psychophysiological state and reducing aggression was described. Results of an experimental study of aggression in adolescents (aggressive behavior, aggression in interpersonal relationships, unrestraint in adolescents) and the psycho-correctional program “Optimizing the level of aggression in adolescents using music therapy” developed on the basis of this study were presented. Results of the follow-up diagnostics of aggression in adolescents after implementation of this program were laid out. It was noted that after the experimental group underwent music therapy, the intensiveness of shift toward reduction of aggression was significant. The following particularities of applying music therapy in the adolescent age for the purpose of overcoming manifestations of aggression have been discovered: the use of the group and individual listening method (the listening in headphones is especially liked); the use of individual thematic “playlists”, meditation under relaxing music, listening to classical music; the use of modern methods of finding music (YouTube, Facebook and other); doing physical exercises under energetic music to vent negative emotions. In sum, the use of the music therapy method proves effective when working with adolescents on reducing their aggression